92.4k views
4 votes
PLEASE HELP! No phony answers, thanks! Happy holidays, Merry Christmas!!

PLEASE HELP! No phony answers, thanks! Happy holidays, Merry Christmas!!-example-1
User Rok Kralj
by
4.7k points

1 Answer

4 votes

Explanation:

(f+g)(x) means we just add the 2 functions, so we have

(x-3) + 2x² = 2x² + x - 3

(f-g)(x) means we subtract g(x) from f(x), so we have

(x-3) - (2x²) = -2x²+x-3

Assuming that the dot signifies a multiplication sign and not a composition sign, we have

(f*g)(x) = f(x) * g(x)

= (x-3) * 2x²

= 2x³ - 6x²

Plugging -2 in, we get

2(-2)³-6(-2)² = -16 -24 = -40

User Kristofor Carle
by
5.0k points